FIZIKA PÁNINE QÍZÍǴÍWSHÍLÍQTÍ QÁLIPLESTIRIW - Karlıbaeva, G.; Matjanov, N. (SCIENCE and SOCIETY, 2017)
The article deals with one of the important issues in methods of the teaching Physics-to include those topics in speciality that promote to increasing motivation and interest, forming scientific views of students and teachers.